The Effectiveness of Educational Policy Implementation in Rural Primary Schools in Guangxi China and Thailand - Fu, Qi; Kaewsopa, Wanchai (ASEAN Journal of Education, 2023)
Rural primary education plays a key role in economic development, and it is also important for sustaining growth in many countries. This article, therefore, sets forth a descriptive method for investigating the approaches to implement educational policies in rural primary schools in Guangxi, China and Thailand. Principals of rural primary schools are purposely selected to express their policy implementation perceptions on the open-ended questionnaires. Their expressions are identified, analyzed, and synthetized to summarize the meaning and essence of information. To ensure data accuracy, the final result is confirmed by respondents, and reviewed by educational experts. The findings indicated that rural primary schools in Guangxi, China and Thailand adopted the corresponding approaches to implement educational policies for achieving goals as in policy formulation process, action plan process, stakeholders’ participation and collaboration, teachers and staff encouragement, monitor and control process, assessment and improvement process, and transparency. Yet schools placed little emphasis on staff training with new and necessary skills. Nevertheless, policy implementation of rural schools in Guangxi, China may lean toward regulations and bureaucracy or chains of command, and the encouragement system may focus primarily on the reward and punishment. Whereas rural schools in Thailand promoted the involvement of teachers and other staff, and encouragement was implemented with a staff engagement approach. The author recommends that school executives should encourage teachers and staff to learn new and necessary skills and utilize the assessment results to implement new policies earnestly.